Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Pemahaman Konsep Segi Empat pada Siswa Kelas VII MTs. Islam Darunnadwah Tahun Pelajaran 2022/2023 - Sabrun, Sabrun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The implementation of learning so far has only been carried out by teachers by providing material conventionally, this has happened during learning at MTs. Darunnadwah Islam which has an impact on the lack of activity and interest of students when learning Mathematics in class, the lack of students' ability to absorb and understand the material provided by the teacher is shown in the low student learning outcomes. The purpose of this study was to find out how the application of problem-based learning models can improve the understanding of the quadrilateral concept in class VII MTs students. Islamic Darunnadwah for the 2022/2023 academic year. This type of research is Classroom Action Research (CAR), which consists of two cycles. The instruments used are observation sheets and tests. From the research that has been done, it shows that there is an increase in students' understanding of concepts, namely in cycle I the average score of students' understanding test results is 75.00 with a completeness percentage of 67.65% because their classical mastery has not yet reached an indicator of success in research, namely 85%, so it is continued to cycle II. Whereas in cycle II the average student understanding test result was 76.29 with 91.17% completeness. For data analysis of student learning activities increased from quite active to very active, so that in this study it was concluded that the application of a problem-based learning model could increase the understanding of the quadrilateral concept in class VII MTs students. Islamic Darunnadwah for the 2022/2023 academic year.